Pengaruh Social Comparison Terhadap Subjective Well-Being Mahasiswa Pengguna Instagram Di Fakultas Psikologi Universitas Muhammadiyah Gresik - Akbar Nugraha; Muhimmatul Hasanah; Ima Fitri Sholichah (Universitas Muhammadiyah Gresik, 2023)
Social comparison is an unavoidable activity when using the social media platform Instagram. This activity can have an impact on the subjective well-being of psychology students at Muhammadiyah University Gresik who use Instagram. The study aims to determine the influence of social comparison on the subjective well-being of these students. A total of 70 students participated in this research using the Incidental Sampling Technique. The method used is a quantitative approach. Data collection was conducted using scales, namely the Satisfaction with Life Scale (SWLS), Positive Affect Negative Affect Schedule (PANAS), and Iowa Netherlands Comparison Orientation Measure (INCOM).The results of the simple regression analysis indicate that the influence of social comparison on subjective well-being is 8.4%, showing an insignificant effect. Thus, students' efforts to avoid excessive social comparison can enhance their subjective well-being, although other factors that could improve students' subjective well-being need to be further examined. Keywords: Social Comparison, Subjective Well Being, college students